Strategi Citra Merek dan Kualitas Produk dalam meningkatkan Loyalitas Konsumen Alamic di TikTok - Nabilah Wanda Vania; Wilma Cordelia Izaak (Universitas Pahlawan Tuanku Tambusai, 2026)
The rise of social media, particularly TikTok, has changed consumer’s perceptions of how they discover, evaluate, and decide to purchase personal care products. This phenomenon has prompted several soap brands, including Alamic soap, to build a strong brand image and maintain product quality to foster sustainable consumer loyalty. This community service project aims to directly engage with Alamic business owners in implementing brand image and product quality strategies to enhance consumer loyalty toward Alamic soap through the TikTok social media platform. The approach used in this community service project involves direct engagement (active participation) by the participants as part of the marketing team in creating digital marketing content and conducting live shopping sessions. These activities serve as a means of disseminating science and technology to Alamic business owners to help them convey their brand image and product quality to consumers via the TikTok platform. This project demonstrates that such direct engagement can enhance consumer loyalty by strengthening brand image and product quality.